Numerical Investigation of Film Cooling Using RANS and LES. (2015) - Li, Shuo; Zhan, Jiemin; Gong, Yejun; Hu, Wenqing
Abstract: Film cooling of turbine blades is an effective way to cool the blade and ensure the long life of turbine blades. Numerical simulation of the film cooling process requires the accurate prediction of the vortex flow in the near wall region. This study compared several popular turbulence models, the realizable k-ɛ model, the k-ω SST model and the LES model. The dimensionless temperature distributions are compared for these turbulence models, and only LES is able to capture the small detachment of the main flow from the turbine blade surface. More details of the pressure, temperature, vorticity and film cooling effectiveness profile are shown in streamwise and spanwise direction for the LES case. Film cooling becomes weaken once the flow detaches from the blade surface.